LEONTIEF MATRIX: BUSINESS MODEL RECOMMENDATION FOR EXPORT COMMODITY OF NORTH SUMATERA - Nur Khasanah; Nikken Prima Puspita; Fitriana Hasnani; Meryta Febrilian Fatimah; Zakaria Bani Ikhtiyar (Jurnal Matematika UNAND, 2026)
The open model as the one the application of Leontief model using the explanation of the economy with input-output model. The open model shows the number of productions needed to satisfy an increase in internal and external demand. By using the operation linear algebra operation on ring characteristics, then the production numbers are calculated. This method is applied on the ten product-producing commodities of North Sumatera export demand to find the total production number, while the amount of demand is defined. It shows a solution to the minimization linear program is the solution that will satisfy both internal and external demands of the commodity with minimum inventory level.